Hubungan Kemampuan Profesional Guru dan Pemanfaatan Sumber Belajar dengan Prestasi Belajar IPA Siswa Kelas V Sekolah Dasar - M.I. Sri Widadi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
The Relationship between Teachers' Professional Competence and Utilization of Learning Resources and Students Achievement in Science. This study was intended to investigate the relationship between teachers' professional competence and utilization of learning resources and students' achievement in science. The study involved 34 elementary school teachers in Sarangan, Surakarta. Product moment technique and regression analyses were employed to analyze the data which had been collected using questionnaires. The results indicate that there is no correlation between the utilization of learning resources and students' achievement in science, that there is a significant correlation between teachers' professional competence and students' achievement, and that there is no significant correlation between the use of learning resources, teachers' professional competence, and students' achievement in science.